2017
DOI: 10.1139/as-2016-0012
|View full text |Cite|
|
Sign up to set email alerts
|

Limnological evolution of Zelma Lake, a recently drained thermokarst lake in Old Crow Flats (Yukon, Canada)

Abstract: Evidence from remote sensing studies suggests that the frequency of thermokarst lake drainage events is increasing in response to climate change, but the consequences of these changes on the limnology of remaining waterbodies remain unknown. Here, we utilize a multiparameter paleolimnological record and post-drainage water isotope and chemistry monitoring to characterize the limnological evolution of Zelma Lake in Old Crow Flats, Yukon. During the early part of the record (~1678 to 1900 CE), analysis of geoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Our DTLB record from WP283 exhibits a δ 18 O increase of ~2.7‰ through time immediately preceding lake drainage. This relict δ 18 O signature may reflect evaporative enrichment of residual lake waters following a partial drainage scenario (Figure 5B), which is known to occur presently in the Old Crow Flats 53 . The WP283 record also shows an ~5.0‰ decrease in d‐excess below the silt–peat interface.…”
Section: Discussionmentioning
confidence: 88%
“…Our DTLB record from WP283 exhibits a δ 18 O increase of ~2.7‰ through time immediately preceding lake drainage. This relict δ 18 O signature may reflect evaporative enrichment of residual lake waters following a partial drainage scenario (Figure 5B), which is known to occur presently in the Old Crow Flats 53 . The WP283 record also shows an ~5.0‰ decrease in d‐excess below the silt–peat interface.…”
Section: Discussionmentioning
confidence: 88%
“…Within days, the lake had lost well over 80% of its water volume, exposing over half of the lakebed (Wolfe and Turner 2008). Our previous studies at Zelma Lake showed that nutrient and ion concentrations increased and became highly variable during 2007-2011, and the lake transitioned to anoxic conditions as indicated by the presence of okenone, a carotenoid pigment produced by purple-sulfur bacteria, within the lakebed sediment (Tondu et al 2017). During this time, the intermittent and remnant water bodies within the Zelma Lake basin underwent reduced residence time with ongoing lateral drainage through the new outlet in addition to evaporation.…”
Section: Introductionmentioning
confidence: 98%
“…Notably, organic matter content at Zelma Lake does indeed increase following observed drainage in 2007 (the sediment core was obtained in 2010) providing additional support for the use of Fig. 6b, although other evidence suggests that aquatic productivity during the post-drainage phase has been much greater than prior to expansion (Tondu et al 2017). It is notable that the timing of these drainage events, based on 210 Pb chronologies extrapolated downcore (where available), is highly variable, suggesting episodic occurrence.…”
Section: Old Crow Flats Northern Yukon Territorymentioning
confidence: 58%